Long-term Ambulatory Change After Lower Extremity Orthopaedic Surgery in Children With Cerebral Palsy. Issue 3 (April 2015) - Yu, Stephanie; Rethlefsen, Susan A.; Wren, Tishya A. L.; Kay, Robert M.
<x xml:space="preserve">Abstract</x> Background: Long-term studies of lower extremity orthopaedic surgery in children with cerebral palsy (CP) tend to focus on gait kinematics and kinetics, with little to no emphasis on gross motor ambulatory function. The current study was undertaken to examine the long-term impact of surgery on ambulatory function in patients with CP enrolled in a government-funded, outpatient therapy program. Methods: Retrospective medical record review was conducted of 127 children with CP, Gross Motor Function Classification System (GMFCS) levels I to IV, followed up to 14 years after lower extremity orthopaedic surgery. Data were extracted from medical/operative records and routine physical therapy evaluations performed over the course of follow-up. Functional Mobility Scale (FMS) scores were assigned based on gross motor function information contained in each 6- to 12-month physical therapy evaluation. Data were compared statistically among GMFCS levels. Results: Average length of follow up was 11.8±4 years. Subjects underwent 0.61±0.43 surgical procedures per person-year in 0.16±0.09 operative sessions per person-year with no differences between GMFCS levels. Subjects at GMFCS level I improved significantly in community (P=0.02) but not household ambulation, reflecting the ceiling effect of the FMS. Subjects at GMFCS levels II to IV showed statistically significant improvements at all distances. Subjects at level III gained more in household than long-distance ambulation (P=0.002). Subjects functioning at GMFCS level II improved by 1 FMS level for household and school distances, and 2 FMS levels for community distances (P<0.02). Subjects at level IV exhibited small ambulatory gains at all distances (P<0.04). Conclusions: Significant long-term improvement in functional ambulation is seen after surgery for children at all GMFCS levels. Children with more independence tend to make gains in long-distance ambulation, whereas those who use assistive devices tend to improve more in short-distance ambulation. This information may be useful to clinicians when counseling patients and their families regarding potential for ambulatory improvement after lower extremity orthopaedic surgery. Level of Evidence: Level IV: case series.